The Effect of Toluene Solution on the Hydrogen Absorption of the Mg-Ti Alloy Prepared by Synthetic Alloying - H. Suwarno; W.A. Adi (PPIKSN-BATAN, 2009)
The synthesis and characterization of the Mg–Ti alloy have been carried out through a mechanical alloying technique under toluene solution. The Mg and Ti powders are milled for 10, 20, and 30 h in a high energy ball mill. The milled alloys are then hydrided at a temperature of 300 oC in order to investigate the possibility used for hydrogen storage materials. The refinement analyses of the x-ray diffraction patterns show that mechanical alloying of the Mg–Ti powders under toluene solution results in the formation of the TiH2 and Mg2Ti phases. Quantitative analyses indicate that the mass fractions of the TiH2 and Mg2Ti phases are 62.90 % and 30.60 %, while the value for Mg and Ti amount to 2.6 wt% and 1.25 wt%. On hydriding at a temperature of 300 oC, the milled powders are transformed into Mg2TiH4, TiH2 and γ-MgH2 phases with the mass fractions of 25.48 wt%, 64.0 wt%, and 10.52 wt%, respectively. Microstructure analyses show that before milling the shape of particle is mostly a ball shape, after 30 h of milling the shape of particles changes into polygonal shape, and upon hydriding the shape of particles changes from a polygonal shape into an irregular one. The final composition of the specimen after hydriding exhibits that Mg-Ti alloy can be promoted as a hydrogen storage material.Received: 27 January 2009; Revised: 19 November 2009; Accepted: 24 November 2009